LGBTfobia e o sistema de segurança pública: análise do atendimento às vítimas - Amorim, Jussyara Paiva (2018)
The following study sought to analyze the confrontation of LGBT-phobia in the Public Security System, regarding, in particular, the assistance to the victims of this crime carried out by the Police Against Homophobic Crimes of the State of Paraíba. DECH / PB is a pioneering and unique safety tool in Brazil. The study pursued to investigate whether the actions developed by this police station have indeed contributed to the registration and referral of the complaints of victims of the crimes committed against the LGBT population. The starting point was based on the assumption that the "naturalization" of this violence is articulated with the determinant principles of capitalist socialization, where sexism and conservative vision of the masculine and feminine roles persists as an important strategy in the dynamics of the domination of this system.In order to collect and investigate the indicated problem, the quantitative-qualitative bibliographical and documental research method was used. In this process, the method of dialectical historical materialism is presented in the perspective of presenting a propositional and critical work. In the data collection phase, we characterize the identification composition of LGBT-phobic victims by age, level of education, affective-sexual orientation and / or gender identity and residence, and also with the crimes denounced for their criminal typification, circumstances and referred to the System of Criminal Justice. According to the analyzed data, the composition by identification mainly demonstrate that the majority of investigated cases have shown, among the victims, teenagers and young adults, an occurrence that decreases along with increasing age, and also that most of the victims have low educational level and lower income, which leads them to reside in areas with higher population concentration, considering the sample analyzed. Regarding the composition by criminal typification and circumstances of the crimes, the results reveal that the majority occurred in public area, being described as crimes of "less offensive potential". In portraying data of lives harmed by various forms of discrimination and violence, we aim to broaden knowledge about the subject and the recognition of people's freedom.